Health-Related Quality of Life after Cystectomy and Urinary Diversion for Bladder Cancer - Cheryl Shih; Michael P. Porter (Advances in Urology)
With multiple options for urinary diversion after radical cystectomy for bladder cancer that have comparable cancer control and complication rates, health-related quality of life (HRQOL) has become an important consideration. This article reviews the methods for defining HRQOL, the challenges in measuring HRQOL in bladder cancer, and the literature comparing HRQOL after various methods of urinary diversion. Recent contributions include the validation of HRQOL instruments specific to bladder cancer and the publication of several prospective studies measuring HRQOL outcomes after cystectomy and urinary diversion. There is no convincing evidence from existing literature that any particular method of urinary diversion offers superior HRQOL outcomes. Rather, there is growing evidence that good HRQOL can be achieved with patient education and consideration of each patient's clinical and psychosocial situation. Future research should utilize the validated bladder cancer specific HRQOL instruments and perhaps explore the impact of preoperative counseling on postoperative HRQOL.